A finite volume scheme for the shallow-water system with the polynomial reconstruction - Clain, Stéphane (2012)
We present a new very high-order finite volume scheme for the shallow-water system based on the local Polynomial Reconstruction Operator (PRO-scheme) and the MOOD technique to guaranty the solution stability. We detail the design of the scheme and provide two examples with regular solution of wave propagation to highlight the scheme capacity to preserve the waves.